TERMINATION OF CONTRACT OF SERVICE (EMPLOYMENT) ACCORDING TO STATUTORY PROVISIONS – A LEGAL STUDY - Dr. B. Someswararao, Mrs. V. N. Roselin, Mrs. B. Keerthi, Mr. Manoj Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The contract of service is an agreement between employer and workmen as to the conditions of employment. The relations between the two persons as employer and workman start from the moment a contract is entered into by them. It is called a contract of service (employment). The determination of contract of service resulting in the termination of service of a workman is subject to several legal restrictions, imposed to secure the interest of workman and not to give a free hand to the employer exercising the labour philosophy of ‘Hire and Fire’. Labour Laws enunciate the restrictions on termination of the relationship of employer and workman besides the contract of service itself. The contract of service is still pivotal despite several statutes made in regulating the relations between employer and workman. It is the focal point both in creating as well as terminating the employment relationship. In Indian context, the most important statutory interventions are The Industrial Disputes Act, 1947, The Industrial Employment (sanding orders) Act, 1946 besides others. Added to them are the decisions by the Apex Court and several High Courts interpreting these statutes in particular and the legal relation emanating from a contract of service in particular. This paper aims at making an attempt to discuss the various modes of termination of employment as per the above-mentioned statutory provisions.